GluN2B-containing NMDA receptors and AMPA receptors in medial prefrontal cortex are necessary for odor span in rats - Davies, Don A.; Greba, Quentin; Howland, John G. (Frontiers in Behavioral Neuroscience, 2013)
Working memory is a type of short-term memory involved in the maintenance and manipulation of information essential for complex cognition. While memory span capacity has been extensively studied in humans as a measure of working memory, it has received considerably less attention in rodents. Our aim was to examine the role of the NMDA and AMPA glutamate receptors in odor span capacity using systemic injections or infusions of receptor antagonists into the medial prefrontal cortex. Long Evans rats were trained on a well-characterized odor span task. Initially, rats were trained to dig for a food reward in sand followed by training on a non-match to sample discrimination using sand scented with household spices. The rats were then required to perform a serial delayed non-match to sample procedure which was their odor span. Systemic injection of the broad spectrum NMDA receptor antagonist CPP (10 mg/kg) or the GluN2B-selective antagonist Ro25-6981 (10 mg/kg but not 6 mg/kg) significantly reduced odor span capacity. Infusions of the GluN2B- selective antagonist Ro25-6981 (2.5 µg/hemisphere) into medial prefrontal cortex reduced span capacity, an effect that was nearly significant (p = 0.069). Infusions of the AMPA receptor antagonist CNQX (1.25 µg/hemisphere) into medial prefrontal cortex reduced span capacity and latency for the rats to make a choice in the task. These results demonstrate span capacity in rats depends on ionotropic glutamate receptor activation in the medial prefrontal cortex. Further understanding of the circuitry underlying span capacity may aid in the novel therapeutic drug development for persons with working memory impairments as a result of disorders such as schizophrenia and Alzheimer’s disease.